A Result of Preparation Program of Knee Replacement Surgery to an Anxiety of the Elderly Patients with Knee Osteoarthritis - พลแก้ว, จิราภรณ์; รอดพาล, จินต์จุฑา (Journal of Preventive Medicine Association of Thailand, 2018)
This research is quasi-experimental research with one group pretest-posttest design. The purpose of this research is to study the result of preparation program of knee replacement surgery to the anxiety of the elderly patients with knee osteoarthritis and also to compare the anxiety of these elderly patients who have the knee replacement surgery before and after joining this preparation program. Experimental instrumentation is the preparation program of knee replacement surgery. Data collection instrumentation is testing of anxiety of the elderly patients who get the knee replacement surgery. This testing is developed from the testing of patients’ anxiety before having a surgery of Veena Loymek (2549) and the confidence level is equal to 0.81. The data is analyzed by percentage, mean, standard deviation and comparison of mean anxiety scores of patients with knee osteoarthritis who have the knee replacement surgery by using Dependent Sample t-test with significant level at 0.05. The result of this research is that the mean anxiety scores of patients with knee osteoarthritis who have the knee replacement surgery after joining the preparation program ( = 2.595, S.D. = 0.217) is less than before joining the preparation program ( = 2.928, S.D. = 0.170) significantly at p<0.001. However, there is only the result of general anaesthetic in No. 9 of report which is different from the others. The result before joining this preparation program of general anaesthetic ( = 2.17, S.D. = 0.99) is not different with after joining the program ( = 2.63, S.D. = 0.76). So, we should apply this preparation program to improve the treatment of the elderly patients with knee osteoarthritis who get the knee replacement surgery in order to reduce the anxiety of them.